Análisis crítico sobre el ensayo m-k de forjados de chapa colaborante - Echevarría, L.; Gutiérrez, J. P. (Revista ALCONPAT, 2012)
The failure of the composite slab is usually produced by the longitudinal slip between the steel sheet and the concrete, which is formed by the interface shear due to vertical shear. As there is no analytic equation that determines the resistance of the slab against this effort once given the geometry of the steel sheet, the resistance is obtained from tests, of which the most used is the m-k test, established by the AISI in 1967. This test is focused on the consecution of two parameters called m and k, that allow us to evaluate the longitudinal shear resistance of the composite slab by using a semi-empirical formula. The aim of this paper is to highlight the limitations of the m-k test for composite slab and identify the additional information that this test can provide.Keywords: composite slab; m-k test; longitudinal shear; analysis; chemical bond.